Rapid Detection of Aspergillus fumigatus Using Multiple Cross Displacement Amplification Combined With Nanoparticles-Based Lateral Flow - Jiang, Luxi; Li, Xiaomeng; Gu, Rumeng; Mu, Deguang (Frontiers in Cellular and Infection Microbiology, 2021)
Aspergillus fumigatus is an opportunistic, ubiquitous, saprophytic mold which can cause infection in the lungs, nose, eyes, brain, and bones in humans, especially in immunocompromised patients. However, it is difficult to diagnose A. fumigatus infection quickly. Here, we introduce a new detection method, namely multiple cross displacement amplification (MCDA) combined with nanoparticle-based lateral flow biosensor (LFB) (MCDA-LFB), which was proved to be fast, reliable, and simple for detecting A. fumigatus. We designed a set of 10 primers targeting the gene annexin ANXC4 of A. fumigatus. The best MCDA condition is 66 °C for 35 min. The minimum concentration that can be detected by this method was 10 fg. In the case of 100 sputum samples, 20 (20%) and 15 (15%) samples were positive by MCDA-LFB and PCR method, respectively. MCDA-LFB and traditional culture method showed the same results. Compared with the culture method, the diagnostic accuracy of MCDA-LFB can reach 100%. It showed that the MCDA-LFB method has better detection ability than the PCR method. We found that the whole process could be controlled within 60 min including the preparation of DNA (20 min), MCDA reaction (35 min) and results reporting (2 min). These results show that this assay is suitable for the rapid, sensitive and specific detection of A. fumigatus in clinical samples.